(untitled) (Research, Society and Development, 2022)
Anxiety, the perception of nursing professionals in the work environment during the COVID-19 pandemic. The aim of the study was to identify the factors that predispose to increased levels of anxiety in nursing professionals. This is an observational, cross-sectional, descriptive study, with quantitative approach, which will be used as an instrument for data collection, sociodemographic questionnaire, test of DASS21- Depression, anxiety and stress scale, applied in two state hospital institutions, located in the city of São Luís - MA. counted with a sample of 109 participants, most professionals presented anxiety in mild to extremely severe levels. The physical and mental suffering of the nursing professional, a common phenomenon due to concerns related to the patient’s suffering, guilt related to restrictions, work-related factors, negative effects on the family and stigma, discrimination and distress. It was evidenced in the study that the shorter the time of work, the higher the level of anxiety, which can be justified due to inexperience, low wages, unhealthy working conditions, besides not having much security if they will remain with the employment relationship.